The influence of water safety knowledge on adolescents’ drowning risk behaviors: a framework of risk-protect integrated and KAP theory - Luo, Shi; Luo, Shulai; Ren, Zhongyu; Zhang, Hui; Li, Xinyu; Liu, Lian (Frontiers in Public Health, 2024)
Introduction Although previous research has examined the risk factors for drowning behavior among adolescents, it is unclear whether this association is influenced by water safety knowledge. This study aimed to examine whether water safety knowledge is associated with adolescents’ drowning risk behaviors and whether drowning risk perceptions and attitudes could have a chain mediating role in the association between water safety knowledge and adolescents’ drowning risk behaviors. Methods This study included 7,485 adolescents from five Chinese provinces and cities. We used the Drowning Risk Behaviors Scales (DRBS) to evaluate the risk of drowning behaviors. The Water Safety Knowledge Scale (WSKS) was used to evaluate the competence level of water safety knowledge. The Drowning Risk Perceptions Scale (DRPS) was used to evaluate the risk level of perceptions, and the Drowning Risk Attitudes Scale (DRAS) was used to evaluate the risk level of attitudes. Results The results of the mediating effect test showed that water safety knowledge (WSK) affected drowning risk behaviors (DRB) through three indirect paths. Drowning risk perceptions (DRP) and attitudes (DRA) have significantly mediated the association between WSK and DRB. In conclusion, DRP and DRA can act as mediators between WSK and DRB, not only individually, but also as chain mediators, where the direct effect is-0.301, the total indirect effect is-0.214, and the total mediated indirect effect is 41.5%. Discussion Water safety knowledge negatively predicts adolescents’ drowning risk behaviors; water safety knowledge has an inhibitory effect on drowning risk perceptions. Water safety knowledge can directly influence adolescents’ drowning risk perceptions and indirectly affect drowning risk behaviors through the mediation of drowning risk perceptions and attitudes comprising three paths: (1) the drowning risk perceptions mediation path, (2) the drowning risk attitudes mediation path, and (3) the drowning risk perceptions and attitudes mediation paths.